Biogeography and conservation status of the pineapple family (Bromeliaceae). Issue 2 (23rd November 2019) - Zizka, Alexander; Azevedo, Josue; Leme, Elton; Neves, Beatriz; da Costa, Andrea Ferreira; Caceres, Daniel; Zizka, Georg
Abstract: Aim: To provide distribution information and preliminary conservation assessments for all species of the pineapple family (Bromeliaceae), one of the most diverse and ecologically important plant groups of the American tropics—a global biodiversity hotspot. Furthermore, we aim to analyse patterns of diversity, endemism and the conservation status of the Bromeliaceae on the continental level in the light of their evolutionary history. Location: The Americas. Methods: We compiled a dataset of occurrence records for 3, 272 bromeliad species (93.4% of the family) and modelled their geographic distribution using either climate‐based species distribution models, convex hulls or geographic buffers dependent on the number of occurrences available. We then combined this data with information on taxonomy and used the ConR software for a preliminary assessment of the conservation status of all species following Criterion B of the International Union for the Conservation of Nature (IUCN). Results: Our results stress the Atlantic Forest in eastern Brazil, the Andean slopes, Central America and the Guiana Highlands as centres of bromeliad diversity and endemism. Phylogenetically ancient subfamilies of bromeliads are centred in the Guiana highlands whereas the large radiations of the group spread across different habitats and large geographic area. A total of 81% of the evaluated bromeliad species are Possibly Threatened with extinction. We provide range polygons for 3, 272 species, as well as newly georeferenced point localities for 911 species in the novel "bromeliad" r package, together with functions to generate diversity maps for individual taxonomic or functional groups. Main conclusions: Diversity centres of the Bromeliaceae agreed with macroecological patterns of other plant and animal groups, but show some particular patterns related to the evolutionary origin of the family, especially ancient dispersal corridors. A staggering 2/3rds of Bromeliaceae species might be threatened with extinction, especially so in tropical rain forests, raising concerns about the conservation of the family and bromeliad‐dependent animal species.